Improving the security of LSB image steganography - Jamil Al-Azzeh; Ziad Alqadi; Belal Ayyoub; Ahmad Sharadqh (Society of Visual Informatics, 2019)
Steganography is the technique of hiding secret data (message) within any media such as digital color image. In this paper we will merge steganography process with cryptography process in order to increase the security of the proposed method. The steganography process will based on LSB method, while the cryptography process will based on generating a huge private key and selecting a special function for encryption decryption. The proposed method will be implemented in order to calculate some performance parameters to prove the efficiency of the proposed method.